1991
DOI: 10.1002/clc.4960140311
|View full text |Cite
|
Sign up to set email alerts
|

Negative u wave during percutaneous transluminal coronary angioplasty

Abstract: Summary:To clarify the clinical significance of the negative U wave during acute myocardial ischemia, the appearance of the U wave and ST-segment elevation on electrocardiography during percutaneous transluminal coronary angioplasty (PTCA) of the left anterior descending artery (LAD group: 11 patients) or right coronary artery (RCA group: 18 patients) was studied. During PTCA, U-wave inversion (newly developed negative U wave, and increased negativity of the pre-existing negative U wave) was observed in 37 (90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the study that the authors analyzed qualitatively, apart from stenosis in LAD, stenosis or spasm was also found in other coronary arteries, namely the left circumflex artery (LCA) and right coronary artery (RCA) 4,5,13 . However, the highest number of inverted U waves found with chest pain was stenosis of the LAD as in the studies of Gurlek et al, Chikamori et al, Miwa et al, Lee Y et al, and Yano et al 2,4,[9][10][11]13,20,21 . Meanwhile, in another study, it was found that when u wave inversion was found, only stenosis was found in the LAD and normal for other coronary arteries.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the study that the authors analyzed qualitatively, apart from stenosis in LAD, stenosis or spasm was also found in other coronary arteries, namely the left circumflex artery (LCA) and right coronary artery (RCA) 4,5,13 . However, the highest number of inverted U waves found with chest pain was stenosis of the LAD as in the studies of Gurlek et al, Chikamori et al, Miwa et al, Lee Y et al, and Yano et al 2,4,[9][10][11]13,20,21 . Meanwhile, in another study, it was found that when u wave inversion was found, only stenosis was found in the LAD and normal for other coronary arteries.…”
Section: Discussionmentioning
confidence: 79%
“…Have been shown to predict a ≥ 75% stenosis of the LAD / LMCA and the presence of left ventricular dysfunction 15 . Meanwhile, several studies stated that there was no clinical presentation in the form of chest pain 3,6,17,18,20,21 . Friedberg et al in 1968 in their case report study stated that patients showed U-wave inversion after exercise induction and complete stenosis of the LAD, but with a normal physical examination without chest pain 6 .…”
Section: Discussionmentioning
confidence: 99%
“…23 The negative U wave has been in addition studied in "dynamic" conditions: exercise testing, PTCA, myocardial infarction, and during angina. 24,25 Positive U waves, for example, are associated with a decreased risk of future cardiac disease. 5 Although all of these studies showed that a negative U wave was highly correlated with disease, none analyzed the U wave in association with T-wave polarity.…”
Section: Discussionmentioning
confidence: 99%
“…1,13 If a resting ECG showed a positive U wave, transient U-wave inversion was defined as present when there was a discrete negative deflection of Ն 0.05 mV within the TP-segment. 14 If a resting ECG showed a negative U wave, transient U-wave inversion was considered to be present when there was an increase in negativity of the wave of Ն 0.05 mV. All ECGs from each patient were interpreted by two independent investigators who were blinded to the study.…”
Section: Estimation Of Ecg Changesmentioning
confidence: 99%
“…During vasospastic angina or coronary angioplasty, U-wave inversion commonly precedes the occurrence of an ST-segment shift and lasts until after the ST-segment shift subsides, as shown in Figure 1. 3,5,14 Interestingly, the maximal degree of U-wave negativity is not necessarily identical to the peak of myocardial ischemia as reflected by the degree of ST-segment elevation. Accordingly, the mechanism responsible for the genesis of U-wave inversion must be different from that of ST-segment shift.…”
Section: Relationship Between Transient U-wave Inversion During Vasosmentioning
confidence: 99%